Occurrence of Intestinal Parasites and Its Impact on Growth Performance and Carcass Traits of Pigs Raised Under Near-Organic Conditions - Li, Yuzhi Z.; Hernandez, Alexander D.; Major, Sara; Carr, Rick (Frontiers in Veterinary Science, 2022)
Parasite infection is a common problem in organic pig production, which can compromise health and growth of pigs, threaten food safety of pork products, and cause economic losses to organic farmers. To develop management strategies for controlling parasites, we evaluated intestinal parasite infection in pigs at different ages and of different sexes, and investigated whether parasite infection influences growth performance and carcass traits in a cross-sectional study. Fecal samples were collected from pigs (n = 298) raised under near-organic standards during nursery, growing, finishing, and gestating phases for analysis of fecal egg counts (FEC) of Ascaris suum, Trichuris suis, and Oesophagostomum spp. Ascaris suum eggs were not detected in feces of nursery pigs. Eggs of Ascaris suum were found in 45%, 74%, and 0% of fecal samples of growing pigs, finishing pigs, and gestating sows, respectively, after false-positive adjustment (P < 0.001). Mean FEC of Ascaris suum was higher in infected finishing pigs than in infected growing pigs (2,502 vs. 724 eggs per gram (epg), P < 0.001). No differences in percent of Ascaris suum positive samples or FEC of Ascaris suum were detected between sexes. Growth performance and carcass traits were not different between non-infected pigs and those infected with Ascaris suum. All pigs (n = 32) examined at slaughter had white spots on the liver, and 78% harbored Ascaris suum worms. Trichuris suis eggs were not detected in any fecal samples. Eggs of Oesophagostomum spp. were found in 7%, 0%, 1%, and 9% of fecal samples of nursery pigs, growing pigs, finishing pigs, and gestating sows, respectively, with a maximum FEC of 40 epg in all age groups. These results indicate Ascaris suum was the predominant parasite infecting growing and finishing pigs in the herds studied. To control A. suum infection, future research should investigate the efficacy of treating pigs with organically approved anthelmintics during the growing phase of production.